How does disgust regulate social rejection? a mini-review - Terrizzi, John A.; Pond, Richard S.; Shannon, Trevor C. J.; Koopman, Zachary K.; Reich, Jessica C. (Frontiers in Psychology, 2023)
The need to belong is a fundamental aspect of human nature. Over the past two decades, researchers have uncovered many harmful effects of social rejection. However, less work has examined the emotional antecedents to rejection. The purpose of the present article was to explore how disgust––an emotion linked to avoidance and social withdrawal––serves as an important antecedent to social rejection. We argue that disgust affects social rejection through three routes. First, disgust encourages stigmatization, especially of those who exhibit cues of infectious disease. Second, disgust and disease-avoidance give rise to cultural variants (e.g., socially conservative values and assortative sociality), which mitigate social interaction. Third, when the self is perceived as a source of contamination, it promotes shame, which, subsequently, encourages withdrawal from social interaction. Directions for future research are also discussed.